2021
DOI: 10.30964/auebfd.742803
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in Learning English by EFL Students in Turkey

Abstract: The purpose of this study is to identify the English language learning difficulties. 2317 secondary and high school students from the state schools of the Ministry of Education in Ankara were included in this study. The data was gathered through the Foreign Language Learning Difficulties Scale (LLDS) developed (2017) by researchers and semi structured interviews. Mixed-method research was used which utilizes both quantitative and qualitative methods. Quantitative data was analyzed through SPSS, a statistical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The current study results are also in line with a study by Özmat & Senemoğlu (2021), they found that poor teaching methods and inadequate learning materials are challenges in the language learning process, where the purpose of this paper is to identify the English language learning difficulties. They analyzed the participants' responds using the Language Learning Difficulties Scale.…”
Section: Discussionsupporting
confidence: 90%
“…The current study results are also in line with a study by Özmat & Senemoğlu (2021), they found that poor teaching methods and inadequate learning materials are challenges in the language learning process, where the purpose of this paper is to identify the English language learning difficulties. They analyzed the participants' responds using the Language Learning Difficulties Scale.…”
Section: Discussionsupporting
confidence: 90%
“…Coşkun 2(2), 2023 EDUCATIONE grammar teaching was mostly regarded as teacher-centered which required students to passively receive the linguistic rules written on the board. It was maintained in the same manner that too much emphasis is put on grammar instruction (Özmat & Senemoğlu, 2021), and especially teaching grammar deductively is thought to be boring in the Turkish EFL context (Uysal & Yavuz, 2015). It is a fact that grammar is perceived as boring by language learners and teachers in other contexts (Jean & Simard, 2011), and the place of teaching grammar is generally considered negatively (Ali El Deen, 2023;Huang, 2023;Loewen et al, 2009).…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…Analyzing various approaches that foreign specialists in linguodidactics use in the practice of teaching English, F. Boers notes that the modern methodology considers vocabulary as one of the integral components of formation and development of speech skills [2]. Vocabulary in the works of D. Özmat and N. Senemoğlu is understood as a set of words that are part of the language [9]. R. Karimian Shirejini and A. Derakhshan define that knowledge of foreign languages has recently become an integral part of the professional competence of many specialists [3].…”
Section: Literature Reviewmentioning
confidence: 99%